Answer

Verified

419.7k+ views

**Hint:**Where we are given a pair of linear equations and we have to find the value of x and y by using the given equation. We can solve the equation by the method of elimination or by using the method of substitution for the method of substitution. First we will find the value of one variable in the form of another for example we will find the value of x in terms of y then substitute that value in another equation. Then we will solve the equation and find the value of that variable. After that substitute the value of that variable in another equation and find the value of the remaining one variable.

**Complete step-by-step answer:**

Step1: We are given a pair of linear equations $3x - 2y = 7$ and $x + 3y = - 5$ by applying the method of substitution we will find the value of both variables. We will solve the second equation for $x$:

$ \Rightarrow x + 3y = - 5$

Subtracting $3y$ from both sides:

$ \Rightarrow x + 3y - 3y = - 5 - 3y$

On proper rearrangement we will get:

$ \Rightarrow x = - 5 - 3y$

Step2: Now we will substitute the value of x in the first equation and solve for $y$:

$ \Rightarrow 3( - 5 - 3y) - 2y = 7$

$ \Rightarrow - 15 - 9y - 2y = 7$

Adding $15$ both the sides we will get:

$ \Rightarrow 15 - 15 - 11y = 15 + 7$

$ \Rightarrow 0 - 11y = 22$

Dividing both sides by$ - 11$:

$ \Rightarrow \dfrac{{ - 11y}}{{ - 11}} = \dfrac{{22}}{{ - 11}}$

$ \Rightarrow y = - 2$

Step3: Substitute $ - 2$ for y in the solution to the second equation at the end of step1 and calculate $x$:

$ \Rightarrow x = - 5 - \left( {3 \times - 2} \right)$

On further solving we will get:

$ \Rightarrow x = - 5 + 6$

$x = 1$

So the solution is $x = 1;y = - 2$

**Hence the solution is $x = 1;y = - 2$**

**Note:**

This type of question we can solve by two methods: first is substitution and the second one is elimination. In this method the main thing is to find the value of one variable in terms of other students mainly doing the mistakes here.

Alternate method:

We are given two equations i.e.

$3x - 2y = 7$…(1)

$x + 3y = - 5$….(2)

Multiply (2) equation by $3$

$3x + 9y = - 15$…(3)

Subtract equation (3) from (1)

$ 3x+ 9y = - 15 $

$ \underline {( - ){{3x}} - 2y = 7} $

$ 11y = - 22 $

Now dividing the both sides by $11$

$y = - 2$

Substitute $y = - 2$ in equation (1) we get the value of x

$ \Rightarrow 3x + 4 = 7$

$ \Rightarrow 3x = 3$

$ \Rightarrow x = 1$

Here also we will get the same solution i.e. $x = 1;y = - 2$

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Which are the Top 10 Largest Countries of the World?

Give 10 examples for herbs , shrubs , climbers , creepers

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

How do you graph the function fx 4x class 9 maths CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Change the following sentences into negative and interrogative class 10 english CBSE